Isolation and Identification Antagonistic Bacterium Paenibacillus tianmuensis YM002 against Acidovorax citrulli - Koo, Young Mo; Heo, A Yeong; Choi, Hyong Woo (Frontiers in Plant Science, 2023)
In this study, we aimed to screen antagonistic microorganisms against Acidovorax citrulli, the causal agent of bacterial fruit blotch, which is known to induce sever diseases in cucurbit crops. From 240 bacterial strains isolated, only one unknown bacterial isolate, named YM002, showed significant antagonistic activity against A. citrulli KACC17909. Further experiments revealed that YM002 shows antagonistic activity against all tested A. citrulli strains, including KACC17000, KACC17001 and KACC17005, to different degrees. The phylogenetic analysis of 16S rRNA sequences identified YM002 as Paenibacillus tianmuensis. Importantly, pretreatment of cucumber (Cucumis sativus) leaves with YM002 enhanced disease resistance as observed by significantly reduced necrotic symptom development and bacterial growth. YM002-induced resistance accompanied by enhanced expression of defense-related genes, such as PAL1, PR1-1a and CTR1. Importantly, culture filtrate of YM002 significantly suppressed biofilm formation and swimming motility of A. citrulli, which is indispensable for its full virulence. In addition to its antagonistic activity, YM002 showed a various plant growth promotion (PGP)-related traits, such as production of ammonia production, amylase production, ACC deaminase production, inodole-3-acetic acid production, extracellular protease production, siderophore production, and zinc solubilization activities. Indeed, treatment of cucumber roots with YM002 significantly enhanced plant growth parameters, such as fresh and dry weight of leaves or roots. This study suggests the potential of YM002 as an effective PGPR with biological control activity against Acidovorax citrulli in cucumber plants.